Association between the triglyceride-glucose index and carotid plaque progression in patients with type 2 diabetes mellitus: a retrospective cohort study - Zhu, Zhangxiang; Xu, Xuan; Wang, Guojuan; Zhang, Qianqian; Li, Ying; Zhu, Jun; Chen, Li; Ye, Qibao; Chen, Mingwei (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index is a novel marker of insulin resistance associated with carotid vascular disease; however, its role in type 2 diabetes mellitus (T2DM) remains unclear.MethodsThis retrospective study enrolled patients with T2DM who underwent repeated hospitalizations at our hospital between 2014 and 2024. Participants were stratified into tertiles based on TyG index values. Multivariable regression analyses were performed to assess the association between TyG index levels and carotid plaque progression.ResultsA total of 548 patients with T2DM (55.93 ± 12.26 years, 60.4% males) were included, with a median follow-up time of 4 (2–7) years. The prevalence of carotid plaque progression increased stepwise with higher TyG tertiles (45.9% vs. 62.6% vs. 57.4%; p = 0.004), and the growth rates of bilateral plaque length and width also increased (all p < 0.05). The positive association between the TyG index and the growth rates of left carotid plaque length, left width, and right width remained significant in the fully adjusted model (TyG, per 1-unit increase: 0.197 mm vs. 0.196 mm vs. 0.189 mm; tertiles of TyG: 0.156 mm vs. 0.162 mm vs. 0.164 mm; all p < 0.05). After multivariable adjustment, Cox regression analysis showed that higher TyG index levels were associated with 1.261-fold, 1.244-fold, and 1.378-fold increased risks of carotid plaque progression in patients with T2DM (all p < 0.05). ROC curve analysis indicated that the TyG index exhibited modest predictive value for carotid plaque progression in patients with T2DM, with an AUC of 0.556 (p = 0.024). Adding the TyG index to the predictive model improved the C-statistic (0.624 vs. 0.649; p < 0.001), NRI = 0.211 (p = 0.015), and IDI = 0.020 (p < 0.001).ConclusionIn patients with T2DM, a higher TyG index is an independent risk factor for carotid plaque progression.